CdS/PbSe Heterojunction Made via Chemical Bath Deposition and Ionic Exchange Processes to Develop Low-Cost and Scalable Devices - José Antonio Heredia-Cancino; Oscar Salcido; Ricardo Britto-Hurtado; Sayra Guadalupe Ruvalcaba-Manzo; Ramón Ochoa-Landín; Santos Jesús Castillo (Applied Sciences, 2021)
Complete optoelectronic devices present major difficulties to be built by aqueous chemical deposition. In this work, a ITO/CdS/PbSe heterostructure was developed, depositing CdS over an ITO-coated substrate via a chemical bath deposition (CBD) technique. The next step involved the growth of a plumbonacrite film over CdS via CBD, where the film acted as a precursor film to be converted to PbSe via ion exchange. The characterization of each material involved in the heterostructure were as follows: the CdS thin films presented a hexagonal crystalline structure and bandgap of 2.42 eV; PbSe had a cubic structure and a bandgap of 0.34 eV. I vs. V measurements allowed the observation of the electrical behavior, which showed a change from an ohmic to diode response by applying a thermal annealing at 150 °C for 5 min. The forward bias of the diode response was in the order of 0.8 V, and the current-voltage characteristics were analyzed by using the modified Shockley model, obtaining an ideality factor of 2.47, being similar to a Schottky diode. Therefore, the reported process to synthesize an ITO/CdS/PbSe heterostructure by aqueous chemical methods was successful and could be used to develop optoelectronic devices.